2018
DOI: 10.1111/ejh.13179
|View full text |Cite
|
Sign up to set email alerts
|

Mate pair sequencing improves detection of genomic abnormalities in acute myeloid leukemia

Abstract: Objective: Acute myeloid leukemia (AML) can be subtyped based on recurrent cytogenetic and molecular genetic abnormalities with diagnostic and prognostic significance. Although cytogenetic characterization classically involves conventional chromosome and/or fluorescence in situ hybridization (FISH) assays, limitations of these techniques include poor resolution and the inability to precisely identify breakpoints. Method:We evaluated whether an NGS-based methodology that detects structural abnormalities and cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 31 publications
(60 reference statements)
0
43
0
1
Order By: Relevance
“…Figure illustrates the gene fusion mechanism along with the abnormal FISH signal patterns that were generated. Conventional chromosome, FISH, and MPseq results for patient 18 with discrepant KMT2A BAP (negative) and KMT2A/MLLT10 D‐FISH (positive) results can be visualized in Aypar et al Briefly, MPseq indicated exons 9‐24 of MLLT10 (NM_004641) were inserted into intron 9 of KMT2A (NM_005933) resulting in a KMT2A/MLLT10 fusion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure illustrates the gene fusion mechanism along with the abnormal FISH signal patterns that were generated. Conventional chromosome, FISH, and MPseq results for patient 18 with discrepant KMT2A BAP (negative) and KMT2A/MLLT10 D‐FISH (positive) results can be visualized in Aypar et al Briefly, MPseq indicated exons 9‐24 of MLLT10 (NM_004641) were inserted into intron 9 of KMT2A (NM_005933) resulting in a KMT2A/MLLT10 fusion.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the full characterization of KMT2A/MLLT10 gene fusions has heavily relied upon a combination of conventional chromosome, FISH, and reverse transcriptase‐polymerase chain reaction studies . To further characterize 2 cryptic KMT2A/MLLT10 fusions with “normal” chromosomes studies (patients 18 and 48), we performed MPseq, a next‐generation sequencing (NGS)‐based assay that resolves chromosomal rearrangements with significantly higher resolution and precision compared to traditional cytogenetic methodoliges . MPseq results for patient 18 detected an insertion of exons 9‐24 of MLLT10 into intron 9 of KMT2A (illustrated in Aypar et al) and predicts an in frame chimeric KMT2A/MLLT10 fusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations